MORFOLOGI LUBANG GEREK DAN PERKEMBANGAN KUMBANG AMBROSIA XYLEBORUS SP. YANG DIPELIHARA PADA MEDIA BUATAN - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1989)
Females of ambrosia beetle Xyleborus sp., one of the most destructive wood boring insects on lone logs (Pinus merkusii), were reared on rubberwood sawdust base media. The media were frepared in test tubes and one famale pertube was then introduced. These cultures were maintained in a dark room at 28°C and 70 % RH for 40 days. Observations were made for number of branches and length of galleries system through the tube walls, and number of progenies produced by the beetles after the media were dissected.It was shown that of the 22 culture tubes, 18 tubes were developed. Most of the beetles extensively tunneled to and fro criss-cross within the media. Mean branch number and gallery length were 16. 7 junction and 46.4 cm tracks ranging 0 - 33 and 0 - 52 respectively. The average of progeny number was 47.9 per tube with one male for about 14. 7 females. It seemed that both number of branches and length of galleries system indicatively correspond to the level of the beetle fecundity.